STROKE NON HEMORAGIK DENGAN FIBROMA VENTRIKEL KIRI - William, Yosef; Putra Gunadhi, I Gusti Ngurah (journal of internal medicine; Vol. 11, No. 1 Januari 2010)
Cardiac ! broma is a rare case. It?s incidents about 3.2% from all incident of cardiac and pericardia tumor, that most often found in infancy and adolescence, and less frequently in adults. Cardiac ! broma is a benign solitary tumor of the heart which is consist of ! brous tissue that most commonly in the left ventricle or the interventricular septum. This case was a male 51 years old with chief complaint of decrease of consciousness about 3 days prior admitted to hospital. He was consulted from neurologist with stroke non hemorrhagic. He was used to be a smoker since young adult. At ! rst time, we found weakness both of extremity, and cardiomegaly without abnormality in heart?s sound. ECG shown inferior old myocardial infarction. The head CT Scan shown there was a infarct in capsulla interna of left sub cortex hemisphere. And from echocardiography, we found there?s a mass on left ventricular with its size was 2 x 2.5 cm. We diagnosed with observation of left ventricular mass caused by probable cardiac myxoma, coronary arterial disease/OMI inferior/FC II, and stroke non hemorrhagic. After two months he had stroke, patient had a total resection of his cardiac tumor. It was done with open heart technique. From histologic ! ndings, we found a white solid mass in macroscopic, and in microscopic, there was ! brous tissue with focal calci! cation at the edge of tissue, which surrounded necrosis coagulated area. One week after surgery, he was went home in well condition and had some medications, i.e. vitamin B complex, acetosal 100 mg od , and captopril 6.25 mg tid. A cardiac ! broma was a rare cardiac tumour. Until now, pathogenesis of cardiac ! broma still unknown. Diagnostic of cardiac ! broma can get from echocardiography and histologic examination. Treatment of cardiac ! broma are symptomatic for its complication, and invasive procedure, i.e. total or subtotal resection, and cardiac transplantation
Keywords: cardiac ! broma, stroke non hemorrhagic, total resection